Gambaran Vaksinasi COVID-19 di Indonesia pada Juli 2021 - Tania Tamara (CV. Jasa Sukses Abadi, 2021)
At the end of 2019, there was a pandemic originating from Wuhan, China. This pandemic is known as COVID-19 (Corona Virus Disease 2019). COVID-19 is caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). When compared with SARS in 2003 the spread of this pandemic was much faster. As of early July 2021, more than 2.3 million positive cases have been reported in Indonesia. The COVID-19 vaccine is available in Indonesia. The government has started a vaccination program as an effort to break the chain of the spread of the Corona virus infection and suppress the number of COVID-19 cases, which is still increasing. When someone gets the vaccine, the body will form specific immunity against the disease that the vaccine can prevent. This person's immune system will be ready to fight the incoming disease-causing bacteria or virus, so that infection does not occur. If a person who has been vaccinated is infected with COVID-19, the symptoms will be lighter and the recovery will be faster. Indonesia has a national vaccination target target of 181 million people, currently 32 million people have received the first dose of vaccination and 14 million people have received the second dose of vaccination. The vaccination program is expected to be one of the solutions to control the spread of COVID-19 in Indonesia.